Abnormal Muscle Activity and Variability Before, During, and After the Occurrence of Freezing in Parkinson's Disease - Cantú, Hiram; Nantel, Julie; Millán, Michelle; Paquette, Caroline; Côté, Julie N. (Frontiers in Neurology, 2019)
Freezing of gait (FOG) is often experienced in advanced stages of Parkinson’s disease (PD) and can lead to an increased risk of falls. Although spatiotemporal characteristics of FOG are well described, their underlying neuromuscular mechanisms remain poorly understood. Several studies have demonstrated an abnormal activation of distal muscles of the lower limb and coordination impairments during gait in people with PD (pwPD). However, few have investigated how various characteristics of electromyograms (EMGs) change before, during and after a freezing episode (FE). Our objective was to quantify changes in proximal and distal leg muscle activity associated with FEs. In this study, twelve pwPD, confirmed as freezers, performed a repetitive stepping-in-place task used to elicit FE. Surface EMGs were collected from proximal (rectus femoris and biceps femoris (BF)) and distal (tibialis anterior (TA) and gastrocnemius medialis (GM)) muscles. Data epochs of 500 ms were extracted from EMG time series at four different periods: baseline, 2 s before a FE, during a FE, and 2 s after a FE. For each epoch, EMG amplitude (root-mean-square (RMS)), variability (coefficient of variation (CoV)), and inter-muscle functional connectivity (mutual information) were quantified. Results from the analysis of 21 FEs show a significant main effect of Period for EMG amplitude in bilateral TA and in the least affected GM (p < 0.01), with decreased activation before freezing that remained low during and after the FE. On the other hand, a main effect of Period was also found in bilateral BF muscles (p < 0.01) but with increased activation before freezing that was generally sustained during and after FE. Main effects of Period were also found for all measures of variability, except for the least affected GM, showing reduced variability during the FE that returned to baseline in all muscles except both TA. Moreover, an increase in functional connectivity between the least affected distal muscles was seen before the FE. Our findings confirm that many characteristics of EMG patterns of both distal and proximal leg muscles change throughout periods of a FE, suggesting both impairment and adaptive strategies from proximal muscles.